Heurísticas para programação da produção em máquina controlada por comando numérico computadorizado - Viviane Junqueira de Moraes (2016)
In this study we treats the production scheduling in a flexible manufacturing system of a small metalworking industry that uses a Computer Numeric Control machine for processing precision parts. The machine performs several jobs that produce products using a set of tools that went be in the magazine so that processing is performed. The magazine of the machine has limited capacity that is lower than the total number of tools required to process all jobs. When a job requires a tool that is not available in the magazine, tool switches are required. The production scheduling is done on a weekly basis, the company has daily work shifts and upper limits for the execution of overtime, and the products have due dates for delivery. Since the overtime is limited, all products may not be delivered within their due dates, incur in late costs. The problem is to determine which jobs should be processed on each day of the planning horizon, the sequence of these jobs and the associated tools loading sequence on the magazine in order to minimize overtime costs and delays costs. This objective is related to reducing the time spent with the setup activities, that is, with the total number of interruptions of the machine and the total number of tool switches. To solve the problem heuristic methods are used for the partitioning of jobs and grouping of the jobs, for the sequencing of the groups of jobs and a search method, capable of refining the costs of the production. The methods developed are tested in instances with real data and the results are compared to the company practice and with an integer programming model. The results obtained, in a reduced computational time, present lower production costs than all the costs of the company practice and for de some instances, the costs are lower than those obtained by the integer programming model.